Pengaruh Persepsi Pekerja terhadap Perilaku Hygiene dan Sanitasi Salon Kecantikan di Kabupaten Merangin Provinsi Jambi - Fauziah Dihanifa; Linda Rosalina (Jurnal Kajian dan Penelitian Umum, 2024)
This study aims to analyze the influence of workers' perceptions on hygiene and sanitation behavior in beauty salons in Merangin Regency, Jambi Province. The research design employed a descriptive quantitative approach with a survey technique. Data were collected through observation, questionnaires, and documentation, involving 23 workers from three salons: Riris Salon, Rumah Cantik, and Salon AA. The findings reveal that workers' knowledge of hygiene and sanitation remains low, negatively impacting the application of workplace health practices. Several behaviors were found to deviate from standards, such as inadequate sterilization of tools and lack of personal protective equipment (PPE) usage. Factors influencing this include lack of training, awareness of risks, and work pressure. The study concludes by emphasizing the need for enhanced training and awareness to improve cleanliness and health standards in beauty salons.